Dysfunctional Endothelial Progenitor Cells in Cardiovascular Diseases: Role of NADPH Oxidase. Issue 1 (January 2015) - Peng, Jun; Liu, Bin; Ma, Qi-Lin; Luo, Xiu-Ju
Abstract : Abstract: Endothelial progenitor cells (EPCs) play a critical role in maintenance of the endothelial integrity and vascular homeostasis, as well as in neovascularization. Dysfunctional EPCs are believed to contribute to the endothelial dysfunction and are closely related to the development of various cardiovascular diseases, such as hypertension, hyperlipidemia, and stroke. However, the underlying mechanisms of EPC dysfunction are complicated and remain largely elusive. Recent studies have demonstrated that reactive oxygen species (ROS) are key factors that involve in modulation of stem and progenitor cell function under various physiologic and pathologic conditions. It has been shown that NADPH oxidase (NOX)–derived ROS are the major sources of ROS in cardiovascular system. Accumulating evidence suggests that NOX-mediated oxidative stress can modulate EPC bioactivities, such as mobilization, migration, and neovascularization, and that inhibition of NOX has been shown to improve EPC functions. This review summarized recent progress in the studies on the correlation between NOX-mediated EPC dysfunction and cardiovascular diseases.